Relationship between Food Contamination Factors and the Presence of Escherichia coli in Juice Drink Outlets in Banjarbaru Selatan Subdistrict - Muhammad Prayogo Pangestu; Rahmawati; Abdul Khair (Jurnal Riset Pangan dan Gizi, 2024)
Juice drinks are one of the beverage snacks that are favored by all circles of society. In South Banjarbaru Sub-district, there are 16 juice drink outlets. As with other food snacks, juice drinks have a risk of contamination by microorganisms, because the manufacturing process is without going through a heating process, so it is necessary to know the factors associated with the presence of Escherichia coli as an effort to prevent bacterial contamination.This study aims to determine the factors associated with the presence of E.coli in juice drink outlets in South Banjarbaru District with a total sample of 16 outlets and juice drink samples. Data collection was done by observation and laboratory tests using the MPN coli method. Based on the results of laboratory tests, 56.3% of the samples met the requirements of Permenkes RI No. 02 of 2023 concerning Regulations on the Implementation of PP No. 66 of 2014 concerning Environmental Health, namely <3.6 MPN/gr or 1.1 CFU/gr. The results of statistical tests showed that there was a relationship between personal hygiene and the presence of Escherichia coli and there was no relationship between the condition of peddler facilities and infrastructure, equipment cleanliness, and food storage and packaging methods with the presence of Escherichia coli in juice drink snack food outlets in South Banjarbaru District. In order to maintain quality and improve personal hygiene, vendors are expected to wash their hands with running water and soap, use gloves/tools, masks and head coverings when handling food, maintain personal hygiene and not wear jewelry.